The effects of grazing on foliar trait diversity and niche differentiation in Tibetan alpine meadows. Issue 9 (14th September 2015) - Niu, Kechang; Messier, Julie; He, Jin-Sheng; Lechowicz, Martin J.
Abstract : Niche differentiation arising in functional trait diversity is expected to increase the potential for species coexistence, but empirical evidence for these relationships is sparse. We test whether grazing increases the functional diversity of leaf traits and niche differentiation in phosphorus limited Tibetan alpine meadows. We measured five traits in the leaf economic spectrum (LES; LC, leaf carbon concentration; LN, leaf nitrogen concentration; LP, leaf phosphorus concentration; SLA, specific leaf area; and LDMC, leaf dry matter content) for all species occurring in grazed and ungrazed plots at each of five sites. By comparing indicators of the fundamental and realized niches of co‐occurring plants in both grazed and ungrazed plots, we quantified a grazing‐mediated competitive effect on trait divergence and convergence. This trait response reflects the relative importance of niche differentiation and competitive exclusion in response to grazing. We found that while grazing induced LP divergence, both LC and LN tended to converge under grazing. Grazing had no effect on either SLA or LDMC diversity. When all five traits are considered together as a functionally integrated suite (LES hypervolume), there is no evidence for either divergence or convergence in response to grazing. Although grazing promotes functionally relevant diversity in LP that enables niche differentiation in competition for scarce soil available P, these results suggest that coordinated shifts in other LES traits sustain effective overall foliar function despite shifts in LP.